DNA methylation as an epigenetic marker of children’s exposure to traffic-related air pollution in Klang Valley, Malaysia - Jalaludin, Juliana; Suhaimi, Nur Faseeha; Abubakar, Suhaili (Springer Science and Business Media Deutschland, 2026)
Purpose: Traffic-related air pollution (TRAP) poses significant health risks to children. While adverse outcomes have been reported, the biological mechanisms underlying these effects remain unclear. This study investigates the association between TRAP exposure and DNA methylation (DNAm) changes in TNFα and CYP1A1 genes as potential epigenetic markers among school children in Malaysia. Methods: A cross-sectional comparative study was conducted involving 248 children aged 7–11 years from high-traffic (HT) and low-traffic (LT) areas in the Klang Valley. Environmental monitoring was performed at both schools and residences to measure levels of PM10, PM2.5, PM1, NO2, SO2, O3, CO, total volatile organic compounds (TVOC), and black carbon (BC). Dietary intake and other potential confounders were assessed via validated questionnaires. Saliva samples were collected and analyzed for DNAm status using methylation-specific polymerase chain reaction (MS-PCR) targeting TNFα and CYP1A1 genes. Results: Pollutant levels were significantly elevated in HT schools (p < 0.001), whereas LT schools recorded higher CO2 concentrations. Children in HT areas had significantly higher methylation in TNFα (54.0% vs. 37.1%; OR = 2.0, p = 0.007) and CYP1A1 (51.6% vs. 37.9%; OR = 1.7, p = 0.030). TNFα methylation was associated with NO2 exposure (OR = 3.0, 95% CI 0.88–1.95, p = 0.036), while CYP1A1 methylation was linked to BC exposure (OR = 2.0, 95% CI 1.02–2.03, p = 0.019). No significant association was observed for residential TRAP exposure. Conclusion: TRAP exposure in school environments is associated with gene-specific epigenetic modifications in children, suggesting potential utility of DNAm as an early biomarker and reinforcing the need for targeted mitigation strategies.